Structure and properties of sintered Al-Cr-Zr alloy. (November 2019) - Agureev, L E; Savushkina, S V; Laptev, I N; Ivanov, A V
Abstract: Aluminum alloy Al-Cr-Zr was obtained by mechanical alloying and spark plasma sintering. The structure, tensile strength, and elastic properties at different chromium contents in the alloy were studied. The best properties both at room and at elevated temperature were shown by Al-0.5% Cr-0.3% Zr alloy samples (Young's modulus ∼65 GPa, tensile strength ∼358 MPa). An increase in the Cr content in the composite to 1% leads to the formation of large chromium-containing inclusions (possibly coarse intermetallic compounds) along the grain boundaries of the alloy, which impairs the mechanical properties of the material.